Biologically Induced Hydrogen Production Drives High Rate/High Efficiency Microbial Electrosynthesis of Acetate from Carbon Dioxide. Issue 4 (13th January 2016) - Jourdin, Ludovic; Lu, Yang; Flexer, Victoria; Keller, Jurg; Freguia, Stefano
Abstract: Electron‐transfer pathways occurring in biocathodes are still unknown. We demonstrate here that high rates of acetate production by microbial electrosynthesis are mainly driven by an electron flux from the electrode to carbon dioxide, occurring via biologically induced hydrogen, with (99±1) % electron recovery into acetate. Nevertheless, acetate production is shown to occur exclusively within the biofilm. The acetate producers, putatively Acetoanaerobium, showed the remarkable ability to consume a high H2 flux before it could escape from the biofilm. At zero wastage of H2 gas, it allows superior production rates and lesser technical bottlenecks over technologies that rely on mass transfer of H2 to microorganisms suspended in aqueous solution. This study suggests that bacterial modification of the electrode surface (possibly via synthesis of Cu nanoparticles) is directly involved in the significant enhancement of the hydrogen production. Abstract : High CO2 fixation rate in the sole form of acetate by microbial electrosynthesis is demonstrated to be driven by biologically induced hydrogen and to occur exclusively within the biofilm, at zero wastage of hydrogen.